1996
DOI: 10.1042/bj3200807
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in bovine opsin can be classified in four groups with respect to their effect on the biosynthetic pathway of opsin

Abstract: Expression in vitro with the recombinant baculovirus expression system showed correct biosynthesis and post-translational processing of "wild-type' bovine opsin with regard to translocation, glycosylation, palmitoylation and targeting. However, several of these processes were severely affected by point mutations. From the overall results of 16 mutants reported here, four groups were distinguished. One group significantly affected neither biosynthesis nor folding of opsin (D83N, P291A, A299C-V300A-P303G). A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The SDS-PAGE analysis also revealed higher bands, which represent oligomers of the pigments. This phenomenon was observed earlier for rhodopsin (DeCaluwé and DeGrip, 1996) and HGH (Vissers and DeGrip, 1996) and has been described for other members of the GPCR family (Javitch, 2004). Functional expression levels of the mutants are similar to that of the wild-type protein (Table 1).…”
Section: Expression Of Recombinant Human Green Cone Pigmentsupporting
confidence: 58%
“…The SDS-PAGE analysis also revealed higher bands, which represent oligomers of the pigments. This phenomenon was observed earlier for rhodopsin (DeCaluwé and DeGrip, 1996) and HGH (Vissers and DeGrip, 1996) and has been described for other members of the GPCR family (Javitch, 2004). Functional expression levels of the mutants are similar to that of the wild-type protein (Table 1).…”
Section: Expression Of Recombinant Human Green Cone Pigmentsupporting
confidence: 58%
“…In contrast to our human data, bovine R69H rhodopsin was table 2 Bioinformatic analyses using three commonly used mutation programs of pathogenicity, SIFT, 37 PolyPhen2, 38 and MutPred, 39 shown previously to produce an abnormally translated protein in a baculovirus expression system. 34 However, we have been unable to confirm a role of R69H in the pathogenicity of retinal disease in Patient 4. A c.206G>A (p.R69H) polymorphic change has been reported once in dbSNP (rs118173887; http://www.ncbi.nlm.nih.gov/projects/SNP), where the frequency of the variant allele is low (0.008, with a heterozygosity frequency of 0.017).…”
Section: Validation Of Functional Analysesmentioning
confidence: 66%
“…Similarly we report a novel R69H variant that was previously reported to be functionally abnormal in a baculovirus system where bovine rhodopsin was used. 34 However, we found that human R69H traffics and functions normally in mammalian cells, suggesting that these inconsistencies may be, in part, because of the use of different assays or, more likely, variation between human and bovine proteins. Again, it is possible that photopigment dimerization, activation/deactivation kinetics, thermal stability, or transducin activation are impaired; however, our current data suggest that this variant functionally behaves in the same way as WT rhodopsin and further analysis would be required to exclude other possible biophysical defects.…”
Section: Original Research Articlementioning
confidence: 82%
“…Functional studies of some rhodopsin mutants in ADRP have led to their classification into distinct groups that implicate misfolding, mistrafficking, and constitutive activity as underlying bases for photoreceptor cell death (Sung et al, 1993;Kaushal and Khorana, 1994;DeCaluwe and DeGrip, 1996;Deretic et al, 1998;Mendes et al, 2005). Yet, a functionally distinct group of mutations is suggested by the Drosophila visual system, wherein light-dependent formation of stable rhodopsin/arrestin complex was implicated in photoreceptor cell death (Alloway et al, 2000;Kiselev et al, 2000;Iakhine et al, 2004).…”
Section: Introductionmentioning
confidence: 99%